L-Carnitine and Its Derivatives in Metabolic and Chronic Diseases: A Narrative Review - Zając, Weronika; Jan Wandzel; Zofia Wandzel; Kamil Kunecki; Aleksander Urbaś; Miłosz Plichta; Rozalia Plichta; Emil Plichta; Katarzyna Wilk; Paulina Wietrzycka (Quality in Sport, 2026)
Background. L-carnitine (LC) is a vitamin-like compound involved in mitochondrial fatty acid transport and energy metabolism. In addition to its physiological role, LC exhibits antioxidant and anti-inflammatory properties. Aim. To summarize current evidence on the clinical applications, therapeutic potential, and safety of L-carnitine in human diseases. Methods. A narrative review of systematic reviews, meta-analyses, and randomized controlled trials published between 2013 and 2025 was conducted using PubMed, Cochrane Library, and Google Scholar. Twenty-nine eligible studies were included. Results. Current evidence indicates that L-carnitine may improve glucose metabolism, insulin sensitivity, lipid profile, neuropathic symptoms, and sperm quality. The strongest evidence supports benefits in metabolic disorders and male reproductive health, whereas evidence for major cardiovascular and reproductive outcomes remains limited. L-carnitine is generally well tolerated at doses up to 2–3 g/day, although prolonged supplementation may increase trimethylamine-N-oxide (TMAO) levels, with uncertain clinical significance. Conclusion. L-carnitine appears to be a promising adjunctive nutritional intervention for selected patient populations. However, additional high-quality randomized controlled trials with long-term follow-up are needed to confirm its efficacy and safety.